Differences in physical fitness levels by adherence to the 24-hour movement guidelines among Japanese elementary school children - Takashi Naito; Kenryu Aoyagi; Koichiro Oka; Kaori Ishii (PLoS ONE, 2025)
Currently, physical fitness levels of Japanese children are lower than in the 1980s. Investigating the relationship between adherence to the 24-hour movement guidelines (24-h MG)—which include moderate-to-vigorous physical activity (MVPA), screen time (ScT), and sleep duration (Sleep)—and physical fitness is crucial for improving children’s fitness. This cross-sectional study examined differences in physical fitness by 24-h MG adherence patterns among children in grades 1–6. Eight fitness components were assessed using standardized tests: handgrip strength (muscle strength), sit-up (trunk muscle strength and endurance), sit-and-reach (flexibility), repeated side jump (agility), 20-meter shuttle run (cardiorespiratory fitness), 50-meter sprint (speed), standing long jump (explosive power), and softball throw (explosive power and dexterity). A total of 307 participants (41.4% male) were included in the analysis. Analysis of covariance was performed, with sex, grade, BMI, and other guideline adherence as covariates. Total fitness scores were significantly higher in those meeting the MVPA (Cohen’s d = 0.47; standardized effect size), both the MVPA and ScT (d = 0.63), both the MVPA and Sleep guidelines (d = 0.65), or with all three guidelines (d = 0.59) compared to those not meeting them. Children meeting the MVPA guideline—either alone or in combination with ScT or Sleep guidelines—showed significantly higher scores in multiple fitness components compared to those not meeting them. When comparing effect sizes, differences in total and most of the individual fitness scores were greater among those who met both the MVPA and either the ScT or Sleep guideline. In contrast, those who did not meet the MVPA guideline but adhered to one or both of the ScT and Sleep guidelines showed no significant differences in total and individual fitness scores. These findings suggest that promoting MVPA adherence is crucial for enhancing physical fitness, and that additionally encouraging appropriate ScT and Sleep behaviors may further improve children’s physical fitness.